A kaleidoscopic view of the territorialized consumption of place. (December 2018) - Cheetham, Fiona; McEachern, Morven G.; Warnaby, Gary
Drawing on Brighenti's (2010, 2014) theoretical exposition of territorology, we extend current conceptualizations of place within the marketing literature by demonstrating that place is relationally constructed through territorializing consumption practices which continuously produce and sustain multifarious versions of place. In our fieldwork, we embrace a non-representational sensitivity and employ a multi-sensory ethnography, thus helping to illuminate the performative aspects of everyday life relating to people who use urban green spaces. Our analysis articulates three key facets relating to the process of territorializing consumption practices: (1) tangible and intangible elements of boundary making, (2) synchronicity of activities, and (3) sensual experiences. Taken together, these facets advance a kaleidoscopic perspective in which spatial, temporal and affective dimensions of the micro-practices of consumption territories-in-the-making are brought into view. Moreover, our empirical research adds an affective dimension to Brighenti's theoretical elucidation of the formation and dissolution of territories, thereby incorporating sensual imaginations and bodily experiences into the assemblages of heterogeneous materials that sustain territories.